Parâmetros estruturais e termodinâmicos de um catalisador bifuncional para desidratação oxidativa do glicerol em ácido acrílico - Lacerda, Lívia Clara Tavares (2016)
The production of biodiesel is constantly rising also increasing the generation of raw glycerol byproduct. Therefore, the search for glycerol conversion routes is of great importance. This work evaluated the properties of the Nb2O5 and Nb2O5/V catalysts treated with H2O2, applied to the oxidative dehydration reaction of glycerol in acrylic acid. All calculations were based on the Density Functional Theory at the level of GGA-PBE and TZP basis set. The peroxo groups originated from the treatment with H2O2 had greater oxidation capacity when compared to those present in the pure catalyst. Furthermore, the catalyst doped with vanadium presented lower energetic costs during the process. These results might aid in designing new catalysts for the production of strategic chemical products from glycerol.